Anti-diabetic combination therapy with pioglitazone or glimepiride added to metformin on the AGE-RAGE axis: a randomized prospective study - Ragazzi, Eugenio; Burlina, Silvia; Cosma, Chiara; Chilelli, Nino Cristiano; Lapolla, Annunziata; Sartore, Giovanni (Frontiers in Endocrinology, 2023)
The ratio between advanced glycation end products (AGEs) and soluble form of receptor (s-RAGE) has been proposed as a risk marker for renal and cardiovascular diseases. The aim of this study was to evaluate in the diabetes condition the influence of two different oral anti-diabetic treatments on the AGE/s-RAGE ratio, during a 5-year observation period. Seventy-three patients with type 2 diabetes mellitus were randomly assigned to a drug therapy with pioglitazone or glimepiride, combined to metformin. Each subject was evaluated at baseline and after 5 years of treatment. In both groups s-RAGE levels did not significantly vary, while the levels of AGE and AGE/s-RAGE were both significantly reduced, basal compared to 5-year values. Within pioglitazone group, as well within glimepiride group, significant variations (Δ, as difference between 5 years of treatment minus basal) were observed for AGE (Δ= ˗21.1±13.4 µg/ml, P<0.001 for pioglitazone; Δ= ˗14.4±11.4 µg/ml, P<0.001 for glimepiride) and in AGE/s-RAGE (Δ= ˗0.037±0.022 µg/pg, P<0.001 for pioglitazone; Δ= ˗0.024±0.020µg/pg, P<0.001 for glimepiride), suggesting an average decrease of the parameters by more than 50% in both treatments. Pioglitazone was more effective than glimepiride in reducing AGE/s-RAGE ratio after 5 years of therapy. These data can help to explain the benefits of oral anti-diabetic therapy in relation to the reduction of cardiovascular risk, as suggested by variations in AGE/s-RAGE ratio as biochemical marker of endothelial function; in particular, treatment with pioglitazone seems to offer greater long-term benefit on AGE-RAGE axis.